Performance Optimization Strategies for High-Concurrency Spring Boot Microservices in Enterprise Financial Systems - Kamalakar Reddy Singi (Eastasouth Institute, 2023)
This paper investigates performance optimization strategies for Spring Boot–based microservices deployed in high-concurrency enterprise financial transaction systems. Although microservices improve modularity and scalability, financial workloads expose bottlenecks related to database contention, synchronous execution, and Java Virtual Machine (JVM) resource management. A coordinated, multi-layer performance optimization framework is proposed, addressing application-level, data-access-level, and runtime-level challenges. The framework is validated using a simulated high-concurrency financial transaction workload. Experimental results demonstrate improved response time, higher throughput, enhanced runtime stability, and reduced error rates under peak load conditions.